Artificial Intelligence, Innovation, and Copyright: Comparing Intellectual Property Law in Indonesia and South Korea - Syafrinaldi Syafrinaldi; Kim Hyeonsoo; Rani Fadhila Syafrinaldi; David Hardiago (Universitas Negeri Semarang, 2024)
The rapid advancement of Artificial Intelligence (AI) is reshaping industries globally, raising critical questions about the intersection of technology, law, and innovation. In particular, AI's ability to autonomously generate creative works challenges traditional concepts of authorship, ownership, and intellectual property (IP) rights. As AI technologies continue to evolve, existing legal frameworks, particularly in the realm of copyright, struggle to keep pace. This issue is especially pronounced in countries like Indonesia, where traditional copyright laws fail to address the complexities introduced by AI-generated content. In contrast, South Korea has made notable strides in reforming its IP laws to accommodate technological advancements, offering a more adaptive approach to regulating AI-driven innovation. This study critically analyzes the adequacy of copyright regulations in Indonesia in the context of AI and compares them with South Korea's more progressive legal responses. The research addresses the urgent need for legal reform in Indonesia to ensure that its IP laws remain relevant in an era of rapid technological change. By examining the regulatory responses of both countries, this study highlights the potential risks and opportunities for innovation that arise from the current legal landscapes. The contribution of this research lies in its comparative approach, shedding light on how differing legal systems address the challenges posed by AI. Through this analysis, the study provides valuable insights into how Indonesia can evolve its copyright framework to foster innovation while protecting the rights of creators, offering a model for countries facing similar technological and legal challenges.